THE USE OF VOCABULARY SELF-COLLECTION STRATEGY TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Muhammad Fauzi Rahman; Rendi Rinaldi; Iman Santoso (PROJECT (Professional Journal of English Education), 2019)
Abstract Generally, problems faced by the students in learning english is the difficulty to learn vocabulary. Any learners or teachers aware that vocabulary is the important element of language proficiency. The practical problem was faced by the 8th grade students of SMP PLUS YPP DARUSSURUR CIMAHI. Based on facts, the Vocabulary Self Collection Strategy (VSS) is a creative teaching and learning strategy to improve students’ vocabulary mastery. VSS is an interractive learning method where students choose words from a text, use contexts and other resources to find out the meaning of the words, and give those words to be learned by others students. The research design of the research was Classroom Action Research (CAR). The results of the study indicate that VSS could improve learning in a class based on a qualitative or quantitative perspective. Based on the results of the qualitative, it could be seen from the classroom situation, the atmosphere of teaching and learning, students participation, and students responses during teaching and learning activities. Meanwhile, quantitative results could be examined from the scores of students in doing the exercises. Thus this research stated that VSS was an effective technique for solving students' practical problems in mastering vocabulary.Keywords : Improve, Vocabulary mastery, VSS, CAR